A Brief Report of Smoking Behaviors in Patients with Incidental Pulmonary Nodules: Associations with Communication and Risk Perception. (April 2019) - Melzer, Anne C; Golden, Sara E; Wiener, Renda Soylemez; Iaccarino, Jonathan M; Slatore, Christopher G
Introduction: Incidental pulmonary nodules (IPNs) are commonly found on routine chest imaging. Little is known about smoking behaviors among patients with IPNs or characteristics of patient-clinician communication that may contribute to these behaviors. We assessed the association of patient characteristics and communication quality with smoking behaviors and stage of change for tobacco cessation among patients with IPNs. Materials and methods: Prospective, repeated-measures, cohort study of current smokers and past-year quitters with IPNs treated within the Veterans Affairs Portland Health Care System. Eligible patients had newly reported, incidental nodules <3 cm planned for non-urgent computed tomography (CT) follow-up. Our primary outcomes were changes in amount smoked and stage of change for tobacco cessation throughout the follow-up period. We used multivariable-adjusted generalized estimating equations for analyses. Results: We identified 37 current smokers and 9 recent quitters. By the final visit, 8 of 36 (22%) baseline smokers had quit and 2 of 7 (29%) recent quitters had resumed smoking. Of 40 respondents, 23 (58%) reported receiving any tobacco treatment (recommendation to quit, medication, and/or behavioral treatment) at least once during follow-up. We found no significant associations of high-quality communication, patient distress, self-perceived risk of lung cancer, and self-reported clinician-recommended smoking cessation interventions with decrease in amount smoked or positive stage of change. Conclusions: Many smokers and recent quitters with IPNs quit during follow-up, though nearly half reported no quit support. We found no association between communication quality or quit support and decreased smoking. The intensity of tobacco treatment offered may have been insufficient to affect behavior.